2011
DOI: 10.1177/1024258911401366
|View full text |Cite
|
Sign up to set email alerts
|

Has European sectoral social dialogue improved since the establishment of SSDCs in 1998?

Abstract: This article looks at the way in which European sectoral social dialogue has developed over the past 20 years. It tries to determine whether the establishment of Sectoral Social Dialogue Committees in 1998 (SSDCs; currently 40) has affected the nature and/or quantity of texts adopted by these bodies. To this end, two periods are considered: 1990—1997 and 1998—2009. A first finding is that European sectoral social dialogue has burgeoned since the mid-1990s. The establishment of SSDCs therefore forms part of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 2 publications
0
15
0
2
Order By: Relevance
“…The other forms are all softer activities based on dissemination of information and learning, which seem to have been transnationalized to a higher degree through exchange of information, joint education/training, exchange of observers or negotiators in collective bargaining and preparation of joint statements. These latter activities are to a high degree conducted within the ETUFs and the ETUC, for which previous research has reported significant levels of cooperation (Degryse and Pochet, 2011;Glassner and Pochet, 2011;Larsson, 2012;Müller, 2016). We now consider the extent to which variations in cooperation depend on industrial relations regime, sector and size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other forms are all softer activities based on dissemination of information and learning, which seem to have been transnationalized to a higher degree through exchange of information, joint education/training, exchange of observers or negotiators in collective bargaining and preparation of joint statements. These latter activities are to a high degree conducted within the ETUFs and the ETUC, for which previous research has reported significant levels of cooperation (Degryse and Pochet, 2011;Glassner and Pochet, 2011;Larsson, 2012;Müller, 2016). We now consider the extent to which variations in cooperation depend on industrial relations regime, sector and size.…”
Section: Resultsmentioning
confidence: 99%
“…Trade union cooperation comprises a varied set of activities with different goals (Larsson, 2012). They range from loose bilateral contacts strengthening national strategies (Müller, 2016;Traxler et al, 2008), to the work in European organizations at sectoral and crosssectoral levels: the European Trade Union Federations (ETUFs) and the ETUC, through which national unions have access to EU policy consultation and negotiations with employer organizations in social dialogue (Degryse and Pochet, 2011;Müller and Platzer, 2017;Perin and Léonard, 2016;Prosser, 2016).…”
Section: Previous Research and Theoretical Assumptionsmentioning
confidence: 99%
“…The new phase also coincided with the increasing importance of sectoral dialogue. As SSDCs expanded numerically and their output proliferated, attention increasingly shifted from the cross-industry dialogue to the sectoral level (Degryse and Pochet, 2011; Keller, 2003a). Nor did the sectoral dialogue go unaffected by the dialogue’s soft turn.…”
Section: Social Dialogue At the European Level: A Cup Half Full Or Empty?mentioning
confidence: 99%
“…Informal joint committees were established very soon in sectors affected by the first European regulations and the launch of the European Coal and Steel Community and the European Economic Community (Dufresne, 2006). Such bodies played at first a consultative role, but the role and status of committees evolved throughout the integration process, and the number of sectors having their own committee grew (Degryse and Pochet, 2011), until there was broad coverage of manufacturing and service activities with 43 committees by July 2016 (Degryse, 2015).…”
Section: The Regulatory Capacity Of the European Sectoral Social Dialmentioning
confidence: 99%